Expert assessment method in studying the problem of forming a positive attitude to life in a family with a special child - Irina D. Demakova (Saratov State University, 2021)
Nowadays, the issues of organizing upbringing and education of a special child are acquiring particular relevance, which is undoubtedly an important factor in the development of institution of education in our country. The purpose of the study is to find effective methods for studying the problems of forming a positive attitude to life in a family with a special child. The idea of the study is to show parents the importance of the problem of forming a positive attitude to life in a family with a special child and of helping their children to live a happy, fulfilling life. The study gives a detailed description of fostering "positive attitude to life" in special children through humane upbringing by parents, teachers and adults. During the study of the above-mentioned problem, we used various empirical methods: observation, conversation, study of documentation and archival materials, analysis of best practices, pedagogical skills, pedagogical innovations, findings and discoveries, analysis of texts, photos and videos, case study. While choosing methods, it was important for us that empirical research would be based not on literary data and scientific concepts, but rather on real reliable facts. The main research method was the method of expert assessment. The obtained materials are presented in the form of 4 blocks of questions and answers: "Do you consider the problem of forming a positive attitude to life in a family with a special child to be an urgent problem?"; "Do you believe that a special child's positive attitude to life can be formed within the family?"; "Do you think that under modern conditions fostering a positive attitude of a child to life is perceived by parents as a pressing problem?"; "Who, in your opinion, can become a family partner in fostering positive attitude to life in a special child?"